Development of a Simulation Scenario Evaluation Tool (SSET): modified Delphi study. (13th December 2019) - Hernandez, Jessica; Frallicciardi, Alise; Nadir, Nur-Ain; Gothard, M David; Ahmed, Rami A
Abstract : Introduction: One critical aspect of successful simulation facilitation is development of written scenarios. However, there are no validated assessment tools dedicated to the evaluation of written simulation scenarios available. Our aim was to develop a tool to evaluate the quality of written simulation demonstrating content validity. Methods: A comprehensive literature search did not yield a validated assessment tool dedicated for the evaluation of written simulation scenarios. A subsequent search yielded six templates published for written simulation scenario design. From these templates, critical scenario elements were identified to create an evaluation instrument with six components of scenario quality with corresponding anchors and rating scale. Subsequently, a national group of simulation experts were engaged via survey methodology to rate the content of the proposed instrument. Ultimately, a modified two-round Delphi approach was implemented to demonstrate consensus of the final assessment tool. Results: 38 responses were obtained in round 1, while 22 complete responses were obtained in round 2. Round 1 kappa values ranged from 0.44 to 1.0, indicating moderate to almost perfect rater agreement for inclusion of the six proposed components. Kappa values specifically regarding scale and anchors ranged from 0 to 0.49. After revisions, there was a significant level of agreement (p<0.05) of all items of the proposed assessment tool in the second-round survey except for item 10. Of note, all initial respondents indicated that they had never evaluated written scenarios with an assessment tool. Conclusions: The Simulation Scenario Evaluation Tool, developed using a national consensus of content experts, is an instrument demonstrating content validity that assesses the quality of written simulation scenarios. This tool provides a basis to guide structured feedback regarding the quality of written simulation scenarios.